1997
DOI: 10.1007/bf01390519
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of intracranial aneurysm associated with pituitary adenoma

Abstract: The incidence of intracranial aneurysm associated with pituitary adenoma is not definitely established although reported higher than in general population. This study was designed to find the existence of such association in a large series of pituitary adenoma cases. A retrospective study of 467 cases of pituitary adenoma (mean age: 41 +/- 15 years) was done. All patients underwent cerebral angiography at least of anterior circulation, detailed hormonal study, and 155 cases had additional magnetic resonance (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 13 publications
(15 reference statements)
4
85
0
5
Order By: Relevance
“…13 Similarly, the recently reported prevalence of intracranial aneurysms has also increased to approximately 2%-5% in patients with brain tumors. 7,8 Specifically, the noninvasive MRA method has been widely used to screen for intracranial vascular abnormalities; furthermore, MRA has power similar to intraarterial DSA in detecting intracranial aneurysms, as there was no significant difference in prevalence in studies with MRA as the initial imaging study compared with DSA as the reference group. 13 Furthermore, the difference in sensitivity between MRA and DSA was not significant in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…13 Similarly, the recently reported prevalence of intracranial aneurysms has also increased to approximately 2%-5% in patients with brain tumors. 7,8 Specifically, the noninvasive MRA method has been widely used to screen for intracranial vascular abnormalities; furthermore, MRA has power similar to intraarterial DSA in detecting intracranial aneurysms, as there was no significant difference in prevalence in studies with MRA as the initial imaging study compared with DSA as the reference group. 13 Furthermore, the difference in sensitivity between MRA and DSA was not significant in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the coexistence of pituitary adenoma and cerebral aneurysm is higher then that with other benign brain tumors in the general population 5 . Approximately 50% of these patients have acromegaly 1,3,[5][6][7][8] , suggesting that high GH and IGF-1 levels or their biological effects might be implicated in the aneurysm's genesis. High IGF-1 induces artery dilation 8 , atherosclerotic and degenerative changes of the artery wall 8,9 , tumor invasion and tumor-directed neovessels 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of pituitary adenoma and cerebral aneurysm is rare, although its prevalence is higher then would be expected in general population [1][2][3][4][5] . We report on an extremely rare condition where growth hormone (GH) -secreting adenoma coexisted with an intrasellar internal carotid artery (ICA) aneurysm.…”
Section: Intrasellar Internal Carotid Aneurysm Coexisting With Gh-secmentioning
confidence: 99%
“…However, the spontaneous rupture of an aneurysm associated with a pituitary tumor 4,7 and pituitary apoplexy associated with an unruptured aneurysm 6 are very rare. Although several cases of unruptured intrasellar aneurysms contiguous to pituitary adenomas have been reported, 5,6,8 the rupture of an aneurysm embedded in a pituitary tumor is rarer 9 : a review of the literature revealed only 1 previous case, 9 in which the rupture of an intratumoral aneurysm caused fatal epistaxis rather than pituitary apoplexy.…”
Section: Discussionmentioning
confidence: 99%
“…7 Thus, the following mechanisms of aneurysm formation associated with pituitary adenomas have been proposed: local circulatory mechanisms, endocrinological mechanisms, mechanical effects, and/or direct invasion. 7 In only one series by Pant et al 4 was this association independent of hormone secretion, size, invasive nature of the tumor, and encasement of the vessels by the tumor; therefore, it was considered to be a simple coincidence. The specific causal relationship between prolactinomas and aneurysms is thus far unknown.…”
Section: Stroke February 2001mentioning
confidence: 99%